Legalisasi Notaris dan Batas Perlindungan Hukum Bagi Para Pihak: Analisis Putusan MA No. 1211 K/Pdt/2025 - Risdi, Muhammad Alqam Alifa (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This article examines the legal status of notarial legalization and the limits of legal protection for parties to underhand agreements, using Supreme Court Decision No. 1211 K/Pdt/2025 as a case study. Employing normative legal research with a descriptive-analytic approach and documentary analysis of court decisions and notarial literature, the study finds that notarial legalization is administrative in nature providing formal certainty regarding signatures and dates but does not transform an underhand deed into an authentic deed nor guarantee the substantive truth of the agreement’s content. The Supreme Court decision confirms that the scope of protection afforded by legalization is limited: the validity and resolution of contractual disputes depend primarily on the contract’s substance, duration, and performance rather than on legalization alone. Practically, notaries should inform parties about these limitations and parties to high-value or high-risk agreements should opt for authentic deeds to secure stronger legal certainty.